Testing for Purchasing Power Parity in Cointegrated Panels - Lyhagen, Johan; Carlsson, Mikael; Osterholm, Par. (Washington, D.C. : International Monetary Fund, 2007)
This paper applies the maximum likelihood panel cointegration method of Larsson and Lyhagen (2007) to test the strong PPP hypothesis using data for the G7 countries. This method is robust in several important dimensions relative to previous methods, including the well-known issue of cross-sectional dependence of error terms. The findings using this new method are contrasted to those from the Pedroni (1995) cointegration tests and fully modified OLS and dynamic OLS esimators of the cointegrating vectors. Our overall results are the same across all approaches: The strong PPP hypothesis is rejected in favour of weak PPP with heterogenenous cointegrating vectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Integrating Vector; WP; Italy